To study awareness about radiation protection Among dental students of chennai-a Questionnaire based study - TAMIZH PAAVAI .THA; JAYANTH KUMAR V (International Journal of Pharma and Bio Sciences, 2017)
The science of radiology is a double edged sword as it carries both benefit and risk to the patient .The primary risk from dental radiography is the rare chance of radiation-induced cancer. During a radiation exposure in the dental office, the individuals exposed to radiation include the dentist, their staff, people in the reception area and members of the public. The aim of this study was to test the students on their understanding of the importance of radiology and its judicious use. The study was carried out with 15 pretested questions which were closed ended. The study reports that there is significance in the number of radiographs being taken by various years of students (P<0.05). However several questions pertaining to the understanding of the ill effects of radiation, radiation protection and use of digital imaging which is technologically advanced with lesser radiation dose were better understood by the CRRI than the other year students (P<0.05) by virtue of their training. This study portrays that the training in radiology protection and radiation biology which is a syllabus for the fourth year (final year) BDS students can be brought in a little earlier to impart better training and make them more aware on the subject.